The Effect of Organizational Culture and Organizational Learning towards the Competitive Strategy and Company Performance (Case Study of East Java SMEs in Indonesia: Food and Beverage Industry) - Wanto, Hary Sastrya (Information Management and Business Review, 2012)
Organizational culture and learning organizations are the major topics of discussion in corporate world. It is well realized that to become learning Organization is to agree a set of attitudes, values and practices that support the process of constant learning within the organization. A learning culture can be developed in an Organization only when the top management and executive is committed and deeply involved. â€œLearning Cultureâ€ should be a Corporate Goal and stated at the highest level of objectives in order that it is cascaded down to the organizations employees and becomes a part of every employeeâ€™s personal, annual goals. It is necessary to establish the relation between culture, learning climate and strategic performance, in order to provide effective direction to the modern organizations. A study has been initiated to analyze the organization culture and organization learning effects toward the Competitive Strategy and Company Performance From the 615 Small and Medium-sized Enterprises in East Javas population, the sample are 143 from the three biggest cities in East Java Indonesia (Surabaya, Malang and Kediri) as the location of this research. This research conducted to apply the Explanatory Research with the Organizational Culture, Organizational Learning, Competitive Strategy and Company Strategy as a Research Variables. Structural Equation Modeling (SEM) was the appropriate tool to examine and to analyze the data. The results of this research showed that Organization Culture has significant effect towards company Competitive Strategy, Organization Learning has significant effect towards Competitive Strategy, but it did not have significant effect towards Company Performance. Moreover, Competitive Strategy has a significance effect towards Company Performance.